2000
DOI: 10.1046/j.1537-2995.2000.40091140.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion in a random sample of hospitals in France

Abstract: General collection of such data, within a system of traceability, could provide relevant denominators from which to interpret adverse-reaction data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
3
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 19 publications
9
54
3
3
Order By: Relevance
“…Excluding blood use in obstetric and gynaecological surgery, Vamvakas and Taswell reported that 51.6% of red cells were transfused to surgical patients, and the French RECERT group found 49% of transfusion recipients were on surgical wards. 5 9 The Sanguis study documented wide variation in transfusion practice across Europe for apparently similar surgical procedures 10. Reasons for the lower surgical transfusion rate in our study could include differences in medical practice, the age profile and health status of our population, or currently evolving patterns of blood use in surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluding blood use in obstetric and gynaecological surgery, Vamvakas and Taswell reported that 51.6% of red cells were transfused to surgical patients, and the French RECERT group found 49% of transfusion recipients were on surgical wards. 5 9 The Sanguis study documented wide variation in transfusion practice across Europe for apparently similar surgical procedures 10. Reasons for the lower surgical transfusion rate in our study could include differences in medical practice, the age profile and health status of our population, or currently evolving patterns of blood use in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the use of red cells and the characteristics of transfusion recipients is limited 25…”
Section: Introductionmentioning
confidence: 99%
“…13 A random sample of hospitals in France also showed that the majority (57%) of transfusion recipients were over age 65. 14 A recent study of RBC transfusion in north England hospitals by Wells and coworkers 9 observed a rapidly rising demand for blood by individuals over the age of 45. In fact, the study found that the majority of blood units (57.2%) were transfused into individuals 65 years and older.…”
mentioning
confidence: 99%
“…The 20 GPs (13 men, 7 women) interviewed were aged 30 to 65, and worked in rural [9], semi-rural [6], or urban [5] settings. They had more than 15 years (12 GPs), 5 to 15 years [5], or less than 5 years [3] of experience of general medicine.…”
Section: Resultsmentioning
confidence: 99%